Discontinuities in the Distribution of Great Wealth: Sectoral Forces Old and New - Leonard Broom; William Shay (Levy Economics Institute of Bard College, 2000)
National surveys of household economics and well-being in the United States usually focus on income. In those income surveys with supplemental wealth modules, the very rich are underrepresented if not unrepresented. Typically, wealth data are truncated such that they do not afford a view of the extreme top of the distribution. Therefore, we attempt to supplement our knowledge about elite wealth holdings by compiling data on the richest individuals and families in the United States. To do so, we draw from the rosters of the "Forbes Four Hundred," which have been published annually by Forbes magazine since 1982. Along with information from other business press reports and standard biographical sources, rosters of the very rich enable research on inequality at the extreme of the wealth distribution during a period of dramatic change in the composition and concentration of wealth. In this study, we focus analytically on economic sectors because we are interested less in the maldistribution of wealth by demographic groups than in inequality between different economic sectors. We will first specify our analytical approach, then examine issues in the use of business press rosters of the very rich as a data source, and follow with a discussion of the dimensions and categories of our sector typology. After presenting our results, we will address how sectoral forces old and new affect economic opportunity and great wealth outcomes.
Keywords: 330